Pengaruh Viral Marketing Dan Celebrity Endorser Terhadap Minat Beli Produk Make Up Azarine - Safa Calista Putri Aulia; Yulis Nurul Aini (PT. Hasba Edukasi Mandiri, 2025)
This study is a study that aims to understand the influence of Viral Marketing and celebrity endorsers on the interest in buying Azarine make-up products. This study is a quantitative type that uses a purposive sampling technique. Data collection was carried out by distributing questionnaires to 100 (one hundred) respondents. In the process of collecting respondent data, it was designed by creating an online questionnaire via Google Form with the intermediary of the message column on the TikTok application for 100 respondents. The sampling technique was carried out using a non-probability sampling technique and combined with the purposive sampling method. Data analysis used in the study that has been carried out using multiple linear regression and coefficient of determination. With the results obtained from this study, it is explained as follows: (1) Viral Marketing (X1) has a positive and significant influence on purchasing interest: (2) celebrity endorsers have a positive and significant influence on purchasing interest: (3) Viral Marketing and celebrity endorsers have a positive and significant influence on purchasing interest.